From emergency to sustainability: shifting objectives in the US Government's HIV response in Tanzania. Issue 8 (3rd August 2017) - Marten, Meredith G.
ABSTRACT: The US President's Emergency Plan for AIDS Relief (PEPFAR) was originally designed as an emergency initiative, operating with considerable funds, immediate roll-out, fast scale-up, and top-down technocratic administration. In a more recent iteration, PEPFAR shifted its focus from an emergency response to more closely account for healthcare sustainability. This transition came on the heels of the 2008 financial crisis, which threatened to stall the 'marvellous momentum' of the 2000's boom in donor aid for global health overall. Now many programmes are having to do more with less as funding flattens or decreases. This paper examines how this transition took shape in Tanzania in 2011–2012, and the successes and challenges associated with it, using participant observation and interview data from 20 months of fieldwork in rural and urban healthcare settings. In particular, I discuss (1) efforts to increase sustainability and country ownership of HIV programmes in Tanzania, focusing on the shift from PEPFAR-funded American non-governmental organisations to Tanzanian partner organisations; (2) principal challenges stakeholders encountered during the transition, including fragmented systems of healthcare delivery and a weakened healthcare workforce; and (3) strategies informants identified to better integrate services in order to build a stronger, more equitable, and sustainable health system in Tanzania.